Testing the validity and reliability of the Korean nursing surveillance scale: a methodological study - Se Young Kim; Mi-Kyoung Cho (BMC, 2024)
Abstract Background Because of the importance of nursing surveillance, there is a need to develop a scale to measure nursing surveillance that reflects the roles of nurses in South Korea. This study aimed to develop a scale to measure surveillance by Korean nurses and to test its reliability and validity. Methods In the development phase, a literature review was conducted to verify the attributes of nursing surveillance, and preliminary items were developed based on the surveillance activities in the Nursing Intervention Classification (NIC) and the interviews of Korean nurses and modified through content validation and a pilot study. In the psychometric testing phase, two surveys were conducted with Korean nurses working in acute hospitals, using the preliminary scale in exploratory factor analysis (EFA, n = 220) and confirmatory factor analysis (CFA, n = 219). Data were analyzed through EFA, CFA, correlation, and reliability analyses to verify convergent validity, discriminant validity, criterion validity, and reliability. To verify the validity of the preliminary scale, the exploratory factor analysis and confirmatory factor analysis convergent validity, discriminant validity, criterion validity, and reliability were performed. Results In the EFA, 16 items were grouped into four factors, accounting for 70.1% of the cumulative variance. In the CFA, the model exceeded the criteria for all fit indices (χ2 = 155.62 [df = 94, p < .001], CMIN = 1.65, SRMR = .048, RMSEA = .055, GFI = .921, NFI = .916, TLI = .955, CFI = .964) and was acceptable. The convergent validity, discriminant validity, criterion validity, and reliability were verified. The final Korean nursing surveillance scale consists of four factors: 'anticipation of problems and decision-making' with six items; 'systematic assessment' with five items; 'recognition of patterns' with three items; and 'identification of the patient's self-care and coping strategies' with two items. Conclusion The Korean nursing surveillance scale developed in this study comprised questions that included NIC's surveillance activities and empirical data from Korean nurses; based on the attributes of nursing monitoring derived from concept analysis, its validity and reliability were verified. This study can provide precedent to motivate the development of nursing surveillance scales in other countries, and ultimately stimulate studies on nursing surveillance, which is essential for patient safety.